Spectroscopic analysis of Pu-bearing compounds in double-walled cells - Villa-Aleman, Eliel; Darvin, Jason R.; Dick, Don D.; Maxwell, Michael C.; Swindle, Ashlee R.; Foley, Bryan J. (Frontiers in Nuclear Engineering, 2024)
Spectroscopic analysis of radiological materials has been historically limited to radiological labs with older or less advanced scientific instrumentation. The development of double-walled cells (DWCs) at the Savannah River National Laboratory (SRNL) has enabled Pu-bearing compounds to be removed from radiological laboratories and studied in our radiologically clean spectroscopy lab with state-ofthe-art instrumentation. In this manuscript, we discuss the contributions of DWCs that have allowed the application of Raman spectroscopy, diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), diffuse reflectance spectroscopy (DRS) in the shortwave infrared, and gamma spectroscopy at SRNL. Significant advances have been made in the understanding of thermal decomposition of Pu(III) and Pu(IV) oxalates, the alpha-induced damage to the PuO2 crystal lattice, and the effect of calcination temperatures to the quality of PuO2. These techniques have enabled methods to conduct PuO2 age dating since last calcination and estimate the calcination temperature with Raman and DRS. Additional spectroscopic information measured with DRIFTS has provided a path to observe the evolution of carbon species with calcination temperature while gamma spectroscopy provides information on age dating since last purification.